Desenvolvimento de controle descentralizado para equilíbrio de correntes em conversores boost paralelo - Vitor Gomes Neves (2024)
Cellular converters are multilevel structures capable of operating relatively independently. This implementation has been increasingly used with the expansion of power electronics aimed at electrical power generation systems and the popularization of electric cars. In these systems, it is important to ensure an equal distribution of current among the cells, and reducing the relevance of communication buses is crucial to ensure system robustness. Thus, this project proposes to develop a completely decentralized current unbalance control for a parallel boost converter, so that, based on the voltage values measured in one cell, the status of the other modules can be estimated. Through simulations in PLECS software, the behaviors of the converter’s electrical variables are defined, an estimator structure is built, and controllers for this system are designed. The behaviors of the equations and controllers are validated by software. Therefore, the boost converter has its estimator and control structured, allowing its use to ensure the balance of the converter’s currents. The tests assessed the system’s ability to operate under different operating conditions, as well as the variation in balancing errors observed. In addition, the ability to reduce current imbalances was analyzed, even with parametric variations in the boost converter inductors.